(untitled) (Bangladesh Journal of Agricultural Research, 2013)
Rose cultivation is now a profitable enterprise to the farmers, but the socioeconomic data and information of this flower are very scarce in Bangladesh. So, the present study was conducted to identify agronomic practices, analyze relative profitability, and input-output relationship during December 2010. A total of 100 rose growing farmers were randomly selected for this study. The results indicated that 100% farmers cultivated Lincoln variety of rose. The costs of rose cultivation were Tk. 3,87,569 and Tk. 2,75,214 per hectare on full cost and variable cost basis, respectively. The major share of full cost was incurred for human labour (30%), followed by land use (23%), fertilizer (17%), and irrigation (12%). The yield of rose was 5,40,107 flowers per hectare. The net return from rose cultivation was Tk. 23,31,196 per hectare. The benefit cost ratios were 2.29 and 1.63 on variable cost and full cost basis, respectively. The highest profit was obtained from rose cultivation compared to its competitive crops like potato+jute, lentil+til and mustard+mungbean for rose. Human labor, land preparation cost, seedling, urea, TSP, MoP and irrigation had positive effect on the yield of rose. Lack of technical knowledge, non-availability of HYV seedling, and infestation of insects and diseases were major problems found in rose cultivation. Government should take necessary steps to overcome these problems. Bangladesh J. Agril. Res. 38(1): 165-174, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15204